KORELASI ANTARA GAYA BELAJAR DAN DISIPLIN BELAJAR DENGAN HASIL BELAJAR IPA SISWA KELAS VIII MTsN 1 PEKANBARU - Futtuhur Rahmah; Darmawati Darmawati; Imam Mahadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study is (i) to find out the learning styles and disciplines of learning for MTsN 1 Pekanbaru students; (ii) to know the correlation between learning styles and learning disciplines by the score of sciences lesson of Students Grade VIII MTsN 1 Pekanbaru. This research was conducted in June-November 2018. The sample used in this study was Grade VIII.9 students and Grade VIII.10 totaling 64 students by purposive sampling technique. The instruments used were learning style questionnaires and study discipline questionnaires. Furthermore, the data was analyzed descriptively and analyzed by product moment correlation analysis at the level of 5% with the student learning result. The results of this study showed that (i) the learning style of Grade VIII.9 students is dominated by the type of kinesthetic learning style and Grade VIII.10 dominated by the type of auditory learning style; (ii) learning discipline students of Grade VIII.9 are in the less category and Grade VIII.10 are in the good category; (iii) for the Grade VIII.9 there is a correlation between learning styles and learning disciplines with student sciences result with the score of correlation coefficient by 0.505 in the medium category on circulatory system material and in the excretion system material by 0.698 strong categories. Whereas in the Grade VIII.10 there is a correlation between learning styles and learning disciplines with student sciences result with the score of correlation coefficient by 0.677 in the strong category of circulation system material and in the excretion system material by 0.724 strong categories.Key Words: Correlation, Learning Style, Learning Discipline, Learning Result.